Teori Belajar Populer (Project Based Learning, Quantum Learning, Self-Directed Learning, Contextual Learning): Array - Ledita Ezy Maulany; Neviyarni; Herman Nirwana (Citra Dharma Cindekia, 2022)
As stated in the National Education System Law (SISDIKNAS) no 20 of 2003 article 3 which states that national education aims to develop the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, competent, creative, independent, and become a democratic and responsible citizen. So to realize these goals, the first steps that must be taken in education, one of which is with educators applying existing learning methods in popular learning theory. There are several forms of learning methods, namely: project based learning, quantum learning, self-directed learning, contextual teaching and learning.